Effect of Fish Amino Acid Application on Growth and N-uptake in Plants Rice Using The System of Rice Intensification Method - Jumar Jumar; Riza Adrianoor Saputra; Siti Raudhatul Jannah (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2021)
Rice is the main rice crop which is used as the staple food of most Indonesians. Rice production in Indonesia cannot be separated from inorganic fertilizers which have a bad impact on the environment, so it is necessary to carry out a revolution, one of which is the SRI method. The addition of FAA organic matter originating from fish sorted by fishermen which have no selling price is used as a substitute for inorganic fertilizers. This study aims to determine the effect of FAA application on growth and N uptake in rice plants using the SRI method and to determine the best dose of the effect of FAA application on growth and N uptake in rice plants using the SRI method. This research was conducted in December 2019 - April 2020 at the Greenhouse of the Agroecotechnology Department, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. The design used was a one-factor Completely Randomized Design (CRD), with treatment f0 (control / without FAA application), f1 (1 mL FAA / L), f2 (3 mL FAA / L), f3 (5 mL FAA / L) , and f4 (7 mL FAA / L). The treatment was repeated 5 times, to obtain 25 experimental units. Observation parameters in the study were plant height, number of tillers, and N uptake of rice leaves. The results showed that the application of FAA with a dose of 1 mL FAA / L was able to increase the height of rice plants by 5.5%, produced an average number of tillers of 14 tillers, and was able to increase nitrogen uptake by 9.6% in rice plant leaves.